1993
DOI: 10.1144/gsl.sp.1993.074.01.29
|View full text |Cite
|
Sign up to set email alerts
|

Field relations, petrogenesis and emplacement of the Bhagirathi leucogranite, Garhwal Himalaya

Abstract: The Bhagirathi leucogranite forms a series of low-angle en echelon, lensoidal intrusions at the top of the High Himalayan slab in the central Himalaya of Garhwal, northern India. The leucogranite comprises the assemblage: K-feldspar + quartz + plagioclase + tourmaline + muscovite ± biotite ± garnet. Compared to other High Himalayan leucogranites it is particularly rich in tourmaline. The granite is generally compositionally homogeneous although it is magmatically banded in both the upper and lower portions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 43 publications
4
41
0
1
Order By: Relevance
“…4), shows several reflectors, which have been successfully matched to the major faults of the Himalaya to the south, notably the STD and the Main Himalayan Thrust (MHT; Hauck et al, 1998;Alsdorf et al, 1998). It has been suggested that the 'bright spots' imaged on the INDEPTH profile beneath south Tibet are leucogranites forming today, at a similar structural horizon and depth to the High Himalayan leucogranites which crystallised during the Miocene and were extruded southward to their present position along the High Himalaya (Searle et al, 1993(Searle et al, , 1997Searle, 1999a,b). It has further been suggested that ages of crustal melt leucogranites in the footwall of the STD decrease to the north (Wu et al, 1998) and that the Greater Himalayan crystalline rocks bounded by the STD above and the MCT below have been effectively extruded southwards from beneath the middle crust of south Tibet (Grujic et al, 1996(Grujic et al, , 2002Searle, 1999a).…”
Section: Deep Crustal Structure From the Indepth Profilementioning
confidence: 97%
See 1 more Smart Citation
“…4), shows several reflectors, which have been successfully matched to the major faults of the Himalaya to the south, notably the STD and the Main Himalayan Thrust (MHT; Hauck et al, 1998;Alsdorf et al, 1998). It has been suggested that the 'bright spots' imaged on the INDEPTH profile beneath south Tibet are leucogranites forming today, at a similar structural horizon and depth to the High Himalayan leucogranites which crystallised during the Miocene and were extruded southward to their present position along the High Himalaya (Searle et al, 1993(Searle et al, , 1997Searle, 1999a,b). It has further been suggested that ages of crustal melt leucogranites in the footwall of the STD decrease to the north (Wu et al, 1998) and that the Greater Himalayan crystalline rocks bounded by the STD above and the MCT below have been effectively extruded southwards from beneath the middle crust of south Tibet (Grujic et al, 1996(Grujic et al, , 2002Searle, 1999a).…”
Section: Deep Crustal Structure From the Indepth Profilementioning
confidence: 97%
“…leucogranite sills (Gansser, 1983;personal observations 2001). These leucogranites all occur in the footwall of the STD (Burg et al, 1984;Searle et al, 1993Searle et al, , 1997, so the ages of the leucogranites constrain the maximum age of brittle faulting along the STD.…”
Section: Geology Of the Eastern Himalayamentioning
confidence: 99%
“…These results support the view that the magma migrated upward with limited, if any, chemical or thermal modifications. There is field evidence that the HHL magmas moved upward through narrow dykes (Le Fort, 1981;Scaillet et al, 1996;Walker et al, 1999), some of which connect to the base of the pluton, such as in the Garwhal Himalaya (Searle et al, 1993;Scaillet et al, 1995a). Harris (1998), together with the P-T conditions inferred for the top and bottom contact aureoles of Manaslu (Guillot et al, 1995a).…”
Section: Conditions During Magma Intrusionmentioning
confidence: 98%
“…The 'bright spots' imaged on the INDEPTH profile beneath south Tibet have been interpreted by some as leucogranitic melts forming today, at a similar structural horizon and depth to the High Himalayan leucogranites which crystallized during the Miocene and were extruded southward to their present position along the High Himalaya (Searle et al 1993(Searle et al , 1997Searle 1999a, b;Gaillard et al 2004). It has further been suggested that the ages of crustal melt leucogranites in the footwall of the STD decrease to the north (Wu et al 1998) and that the Greater Himalayan crystalline rocks, bounded by the STD above and the MCT below, have been effectively extruded southwards from beneath the middle crust of south Tibet (Grujic et al 1996(Grujic et al , 2002Searle 1999a;Searle & Szulc 2005).…”
Section: Deep Crustal Structure From the Indepth Profilementioning
confidence: 99%